APLIKASI KROKOT PADA PENGOLAHAN NAGET SEBAGAI PRODUK PANGAN FUNGSIONAL - Ratih Yuniastri; Ismawati Ismawati; Rika Diananing Putri (BUANA SAINS, 2021)
Nugget is one of the foods consumed by numerous people.  In this study, the raw material for nuggets was tempeh and formulated with purslane to obtain nuggets that contain fiber and are low in fat. This research used three treatment formulations of ingredients and purslane: 95%: 5% (NK1); 90%:10% (NK2); 85%:15% (NK3) and control without the addition of purslane.  The treatments have tested for preference. The best sample based on the preference test was then tested for fiber and fat content and compared with the control. The results of the study found that the best treatment based on the preference test was the addition of purslane 1.62% and NK2 1.87%. The fat content of the control nugget was 15.64% and NK2 was 15.02%.